Effect of Stem Diameter, Cutting Speed and Moisture Content on Cutting Torque for Green Gram Harvesting - Kumar, Sanjay; Mahapatra, M.; Behera, D.; Pradhan, P. L.; Swain, S. K.; Rath, Ipsita; Sahni, Ramesh K. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted during November, 2021 at Department of FMPE, CAET, OUAT, Bhubaneswar, Odisha, India to investigate the torque requirement and ascertain optimum peripheral cutting velocity of rotary cutting disc based on varying stem diameter and moisture content of green gram . The cutting operation was simulated to find the cutting torque in the instrumented soil bin, which comprises of test trolley, processing trolley and vertical rotor assembly with vertical shaft having serrated cutting disc. Sample plant stems of green gram were firmly fixed in the plant stem holder, and buried beneath the soil to simulate the natural standing of the crop as in the actual field condition. The cutting torque required to cut the stem of green gram at different crop moisture content (39.2, 41.4 and 42.9% (wb)), peripheral cutting velocity (20, 25, 30, and 35 ms-1) and plant stem diameter (2.95, 3.97 and 4.96 mm) was measured. It has been observed that peripheral cutting velocity of disc, stem diameter and moisture content of plant affected cutting torque at 1% level of significance. The cutting torque increased with decrease in moisture content and increase in diameter of plant stem of green gram. The cutting torque increased with an increase in peripheral cutting velocity up to the critical velocity of 30 ms-1, but the value decreased after critical peripheral velocity.